A Prelude to Joyce’s Chamber Music - Flor, João Almeida, 1943- (2012)
It seems appropriate not to overlook the documentary value of Chamber Music in so far as it might be profitably approached as a kind of aesthetic laboratory where Joyce experimented with various styles, forms, and modes of expression. In particular, the book documents an early Joycean attempt to explore the interaction between sound and meaning, with a view to the ideal blending of two com plementary discourses, i.e. poetry and music. Such a revaluation would redress the balance in establishing the literary interest of Chamber Music, which might then emerge as a significant step both in the progress of Joyce’s art and in the development of the poetry and poetics of the pre-modernist generation.